The efficacy of gray matter atrophy and cognitive assessment in differentiation of aMCI and naMCI. Issue 1 (2nd January 2022) - Qin, Ruomeng; Li, Mengchun; Luo, Rong; Ye, Qing; Luo, Caimei; Chen, Haifeng; Qian, Lai; Zhu, Xiaolei; Bai, Feng; Zhang, Bing; Liu, Renyuan; Zhao, Hui; et al.
Abstract: Background: Mild cognitive impairment (MCI) is a heterogeneous entity that can be categorized into related but different subtypes. In this study, we analyzed the gray matter structural changes of amnestic MCI (aMCI) and non-amnestic MCI (naMCI), and how it resulted in diverse cognitive impairment. Methods: Altogether 77 individuals were recruited, including 28 cognitively normal controls (NC), 25 naMCI subjects, and 24 aMCI subjects. All participants underwent a 3.0 T magnetic resonance (MR) scan and a detailed neuropsychological examination. Cortical thickness and subcortical nuclei volume were extracted by Freesurfer software and compared among groups. The areas with significant differences were further analyzed by general linear regression to identify the risk factors of each cognitive impairment subtypes. Results: Significant differences were observed in bilateral hippocampi, amygdala, thalamus, accumbens, left transverse temporal gyrus and left precuneus among groups. AMCI and naMCI were significantly different in the right hippocampus, bilateral amygdala, left precuneus, and left transverse temporal gyrus. Linear regression analysis revealed that the atrophy of left precuneus was a risk factor of memory, executive function (EF) and visuospatial impairment ( p  < 0.001). The atrophy of left amygdala, right accumbens and left thalamus were risk factors of memory, EF and language impairment respectively ( p  < 0.05). Conclusions: These findings confirmed that different gray matter structural changes could lead to specific neuropsychological features in MCI subtypes. Thorough understanding of MCI subtypes and the underlying pathology would be beneficial for precise diagnosis and intervention.